Analysis of Language Acquisition in Children Aged 0-5 Years in the Care of Career Mother: Behaviorism Theory-B.F Skinner - Napitupulu, Lilis Handayani; Bako, Evi Novalin (English Language Teaching Prima Journal (ELT), 2024)
This research aims to reveal the language acquisition of children aged 0-5 years old in career-mother’s parenting by using behaviorism theory by B.F Skinner that is language acquisition formed by associative relationship between stimulus and repetitive responses to form reinforcement (habits). The influence of a career mother requires a child to be left at home with a babysitter, so it affects to the language acquisition of the child. This research uses qualitative method with the subject of research is five childrens aged 0-5 years old who the mothers are a ful-time worker and raised by a different babysitter substantially in language teaching for the children. The method that is used in this research is descriptive qualitative method. Directly observation and interview technique are used as data analysis technique. The result of the analysis shows that the pattern of children’s parenting is very influential on the language acquisition. The interaction between a mother and a child or a babysitter and a child is a form of stimulus to the children and repeated responses so that the reinforcement will determine the success of children’s language acquisition. Environtment plays a significant role in language development especially in vocabulary. Therefore, the children need to be involved in a dialogue or conversation, a question and interactive language.